Pengaruh Digital Marketing, Word of Mouth dan Kepercayaan terhadap Keputusan Pembelian Mobil Suzuki pada PT Megah Putra Sejahtera Kota Makassar - Ramadani, Tenri Wahyu; Romadhoni, Buyung; Muchran, Muchriady (Ekonomis: Journal of Economics and Business, 2025)
This study aims to examine and analyze the influence of digital marketing, word of mouth, and trust on purchasing decisions for Suzuki cars at PT. Megah Putra Sejahtera in Makassar. The research adopts a quantitative approach with a survey design. Data was collected through a questionnaire distributed to 160 customers of PT. Megah Putra Sejahtera. The data analysis technique used is path analysis. The results show that digital marketing and word of mouth have a positive and significant impact on customer trust. Trust, in turn, significantly affects the purchasing decision for Suzuki cars. However, the direct impact of digital marketing and word of mouth on purchasing decisions, without the mediation of trust, was not found to be significant. These findings suggest that customer trust is an important mediating variable in the relationship between digital marketing, word of mouth, and purchasing decisions. The study recommends that future research consider additional variables such as service quality, product quality, and reference groups to further enrich the analysis of purchasing decision-making.